(3LegQI GdCeKGds - (3GdMSf Hf YHO Gddg Hf Sgd Hf SYjO GHf jMji Hf egQGf GdnYrSncQj, CHh gdGd,J (B395 (3g` s ((3YHO GdSjO Hf Ydi Hf LYaQ s)
(3ChdgG (B:s
(3CMeO Gddg MeO GdTGcQjf hGdCeKGd CjVkG fhY ef GdYde efaQO HfaSg s
(3BNQgG (B:s
(3hGdYQH Jbhd ge cCjSGQ dbei Hf YHGO bGd WQaI Je cJGH GdCeKGd s
(3GdfSNI HgG MhGTs
(3HChdg agQSs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs